Cross-cultural communication in the international classroom - Beard, Michael (Đại học Quốc gia Hà Nội, 2020)
In most cases, a typical international classroom consists of two or more cultures. With a multicultural group of students there could be as many cultures as there are students. Therefore, because of the factthat an international classroom is by nature multicultural, cross-cultural communication skills are essential skills to learn and incorporate whenever an international teacher or institution decides to cross cultures inorder to teach. The paper will explore various modes of cross-cultural communication (specificallyfocusing on non-verbal forms of communication) and suggest some principles to follow in the international classroom.